Effect of exercising in the heat on intestinal fatty acid-binding protein, endotoxins, and lipopolysaccharide-binding protein markers in trained athletic populations: A systematic literature review - Wallett, A.; Périard, J. D.; Saunders, P.; McKun, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
Along with digestion and absorption of nutrients, the gastrointestinal epithelium acts as a primary intestinal defense layer, preventing luminal pathogens from entering the circulation. During exercise in the heat, epithelial integrity can become compromised, allowing bacteria and bacterial endotoxins to translocate into circulation, triggering a systemic inflammatory response and exacerbating gastrointestinal damage. While this relationship seems clear in the general population in endurance/ultraendurance exercise, the aim of this systematic review was to evaluate the effect of exercise in the heat on blood markers of gastrointestinal epithelial disturbance in well-trained individuals. Following the 2009 Preferred Reporting Items for Systematic Reviewed and Meta-Analyses guidelines, five electronic databases were searched for appropriate research, and 1,885 studies were identified. Five studies met the inclusion criteria and were subject to full methodological appraisal by two reviewers. Critical appraisal of the studies was conducted using the McMasters Critical Review Form. The studies investigated changes in markers of gastrointestinal damage (intestinal fatty acid-binding protein, endotoxin, and/or lipopolysaccharide-binding protein) following acute exercise in warm to hot conditions (= 30 °C) and included trained or well-trained participants with direct comparisons to a control temperate condition (= 22 °C). The studies found that prolonged submaximal and strenuous exercise in hot environmental conditions can acutely increase epithelial disturbance compared with exercise in cooler conditions, with disturbances not being clinically relevant. However, trained and well-trained populations appear to tolerate exercise-induced gastrointestinal disturbance in the heat. Whether this is an acquired tolerance related to regular training remains to be investigated.